2008
DOI: 10.1080/10915810802513619
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Toxicological Potential of Capsinoids: VIII. A 13-Week Toxicity Study of Commercial-Grade Dihydrocapsiate in Rats

Abstract: Dihydrocapsiate, (4-hydroxy-3-methoxybenzyl 8-methylnona- noate; CAS No. 205687-03-2) is a naturally occurring capsinoid compound found in nonpungent chili peppers. Although the safety of synthetically produced dihydrocapsiate has been previously evaluated, the purpose of this 13-week gavage toxicity study is to evaluate dihydrocapsiate produced with a slightly modified manufacturing process. Sprague-Dawley rats, 10 rats/sex/group, 6 weeks of age at study initiation, were administered the dihydrocapsiate daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 13 publications
(16 reference statements)
4
21
0
Order By: Relevance
“…Unassigned animals were euthanized by C02 inhalation. Individual body weights on the day of grouping were in the range of 171 to 250 g. Based on the results of the 13-week toxicity study of the test substance (Watanabe et al 2008c), the low-dose adverse effect level in males (1000 rug/kg/day) was selected as the high dose in this study and half of that dose (i.e., 500 mg/kg/day) was chosen as the low dose. The test substance was dissolved in the vehicle and administered to rats orally once daily for 28 consecutive days by gavage at a volume of 5 ml/kg BW.…”
Section: Gene Mutation Assay In Transgenic Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unassigned animals were euthanized by C02 inhalation. Individual body weights on the day of grouping were in the range of 171 to 250 g. Based on the results of the 13-week toxicity study of the test substance (Watanabe et al 2008c), the low-dose adverse effect level in males (1000 rug/kg/day) was selected as the high dose in this study and half of that dose (i.e., 500 mg/kg/day) was chosen as the low dose. The test substance was dissolved in the vehicle and administered to rats orally once daily for 28 consecutive days by gavage at a volume of 5 ml/kg BW.…”
Section: Gene Mutation Assay In Transgenic Ratsmentioning
confidence: 99%
“…The target organs were selected based on findings in previous studies. The 13-week repeated administration study revealed findings suggesting effects on the liver (Watanabe et al 2008c) and the kidney is the major excretion pathway . Oral administration would result in a relatively high concentration of the test material in the intestinal tract.…”
Section: Gene Mutation Assay In Transgenic Ratsmentioning
confidence: 99%
“…Capsiate is a nonpungent capsaicin-related compound extracted from the fruit of the CH-19 sweet pepper wherein it is highly concentrated [ 2 ]. Chronic administration of capsiate has been reported to promote fat loss in both humans [ 3 ] and rodents [ 4 , 5 ] in the absence of any adverse effect or toxicological changes [ 6 , 7 ]. This anti-obesity effect would be mediated by an acceleration of basal fatty-acid oxidation in mitochondria [ 3 , 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…63 The observed diffuse hepatocellular hypertrophy described corresponds to previously reported findings of hepatocellular hypertrophy/increased liver weights in capsaicin analogue studies. 57,62,64,65 It has been suggested that low incidences are within the normal range for rats 62 and that hepatocellular hypertrophy when observed alone can be an adaptive response. 66 Again, hepatocellular hypertrophy alone is not considered to be of adverse nature.…”
Section: Discussionmentioning
confidence: 99%